Redox-responsive Pickering emulsion derived from the fabricated sheddable polymeric micelles. (5th December 2018) - Yuan, Jun; Deng, Amin; Yang, Duanguang; Li, Huaming; Chen, Jian; Gao, Yong
Abstract: Amphiphilic graft copolymers with cleavable side chains exhibit many superiorities in some fields, such as the encapsulation, drug delivery and release, etc. In this study, we demonstrated a redox-responsive Pickering emulsion that was stabilized by sheddable polymeric micelles with many reversible S-S linkages at core-shell interfaces. The sheddable polymeric micelles were achieved by the self-assembly of amphiphilic polyurethane- g -poly (N, N-dimethyl acrylamide) (PU- g -PDMA) copolymers whose PDMA side chains were tethered on PU backbones by means of the reversible S-S linkages. Such PU- g -PDMA copolymers were synthesized via the combination of the polyaddition reaction with the reversible addition–fragmentation chain transfer (RAFT) polymerization reaction. The structure, molecular weight and molecular weight distribution of the polymers were characterized by 1 H NMR and GPC analysis. Emulsifying experiments indicated sheddable polymeric micelles possessed perfect emulsifying performances, and highly stable oil-in-water Pickering emulsion could be formed at a low content of emulsifiers. At the same time, the S-S reversible linkages retained at core-shell interfaces of polymeric micelles allowed hydrophilic PDMA shells to be detached through the thiol–disulfide exchange reaction under a reductive environment, which also allowed the resultant Pickering emulsions with redox-responsive demulsification. Graphical abstract: Highlights: Novel method for graft copolymers with cleavable side chains was demonstrated. Sheddable micelles exhibiting switchable emulsifying performances were prepared. A novel Pickering emulsion with redox-triggered demulsification was fabricated.